2006
DOI: 10.1111/j.1748-5827.2006.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cholangitis/cholangiohepatitis with or without concurrent cholecystitis in four dogs

Abstract: This report highlights the fact that bacterial cholangitis/cholangiohepatitis with or without concurrent cholecystitis should be considered as a potential differential in dogs presenting with signs referable to biliary tract disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
69
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 19 publications
7
69
1
1
Order By: Relevance
“…However, the true prevalence might be underestimated, as many cases do not undergo liver and bile cultures. Hence, data identifying the most common pathogens obtained from bile cultures from dogs with cholangiohepatitis are also sparse, although E. coli has previously been reported to have been isolated in association with this disease (15). The data presented in the current report advances knowledge by being the first to identify ESBL-producing E. coli in a case of canine cholangiohepatitis.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…However, the true prevalence might be underestimated, as many cases do not undergo liver and bile cultures. Hence, data identifying the most common pathogens obtained from bile cultures from dogs with cholangiohepatitis are also sparse, although E. coli has previously been reported to have been isolated in association with this disease (15). The data presented in the current report advances knowledge by being the first to identify ESBL-producing E. coli in a case of canine cholangiohepatitis.…”
mentioning
confidence: 64%
“…Bacterial cholangiohepatitis is considered an uncommon disease in dogs (22) and slightly more common in cats (15). However, the true prevalence might be underestimated, as many cases do not undergo liver and bile cultures.…”
mentioning
confidence: 99%
“…A similar list of bacterial isolates has been compiled from cats and dogs diagnosed with a broader range of hepatobiliary diseases. [3][4][5][6][7][8][9][10][11][12][13] However, the overall prevalence and antimicrobial susceptibility of the different bacterial species cultured has not been evaluated in a large group of cases. Therefore, the purpose of this retrospective study was to characterize the results of biliary and liver cultures from dogs and cats evaluated for hepatobiliary disease at a veterinary teaching hospital, including the prevalence of positive cultures, the identity and antimicrobial susceptibility of common isolates, and clinical predictors of positive bacterial culture results.…”
mentioning
confidence: 99%
“…1,2 In veterinary patients, bacteria have been isolated from cases of suppurative cholangitis, hepatic abscesses, cholecystitis, choledochitis, and choleliths. [3][4][5][6][7][8][9][10][11][12][13] In humans with biliary disease, certain conditions have been associated with a higher incidence of infection, such as cholelithiasis, cholecystitis, previous biliary-tract surgery, or other causes of obstructive jaundice. [14][15][16][17][18] In these studies, the most commonly identified biliary pathogens in human patients are enteric bacteria (Escherichia coli, Enterococcus spp., Klebsiella spp., Bacteroides spp., and Clostridium spp).…”
mentioning
confidence: 99%
“…A neoplastic cause seems unlikely given the ultrasonographical appearance of the liver and the favourable response to non-specific therapy. An infectious cholangiohepatitis and cholecystitis causing the dog's clinical signs cannot be ruled out although this disorder is not encountered frequently in dogs [8]. In fact, this possibility prompted the decision to initiate antimicrobial therapy.…”
mentioning
confidence: 99%